Pemetaan Sebaran Daerah Potensial Penangkapan Ikan Karang Berdasarkan Parameter Oseanografi Di Perairan Pulau Kerdau Kabupaten Natuna - Jeriyan Jeriyan; Asep Ma’mun; Esty Kurniawati (Amanisal: Jurnal Teknologi dan Manajemen Perikanan Tangkap, 2026)
This study addresses the high fishery potential of Natuna waters, influenced by oceanographic dynamics, while localized mapping of reef fish fishing grounds remains limited. Previous studies have mainly focused on pelagic species and large-scale areas, with limited integration of oceanographic and habitat-based spatial analysis at the local level. This study aims to analyze the relationship between oceanographic parameters and reef fish catch (CPUE) and to map potential fishing grounds around Kerdau Island using spatial analysis and remote sensing. A descriptive survey approach was applied, integrating primary and secondary data collected through observation, interviews, and documentation. Data were analyzed using the Generalized Additive Model (GAM) and Geographic Information Systems (GIS) to develop a Habitat Suitability Index (HSI). The results show that individual oceanographic parameters do not significantly influence CPUE; however, their combination explains up to 73.21% of its variation, with the best model including temperature, salinity, current, chlorophyll-a, and sea level. Optimal fishing conditions were identified within specific parameter ranges. HSI mapping indicates that 61.40% of fishing locations fall within suitable zones (HSI ≥ 0.5), with spatial and temporal variability. However, 38.60% of fishing points remain in low-suitability areas, indicating limitations of the model in capturing all influencing factors. This study is limited by the exclusion of habitat complexity, fishing pressure, and socio-economic variables, as well as a short observation period. Future research should integrate broader ecological and anthropogenic factors to improve model accuracy and support sustainable fisheries management.